A Possible Role of Crustacean Cardioactive Peptide in Regulating Immune Response in Hepatopancreas of Mud Crab - Wei, Yujie; Lin, Dongdong; Xu, Zhanning; Gao, Xiaoman; Zeng, Chaoshu; Ye, Haihui (Frontiers in Immunology, 2020)
Crustacean cardioactive peptide (CCAP), a cyclic amidated nonapeptide, widely found in arthropods; the functions of CCAP have been revealed to include regulation of heart rate, intestinal peristalsis, molt and osmotic pressure. However, to date there has not been any report on possible involvement of CCAP in immunoregulation in crustaceans. In this study, a CCAP precursor (designated as Sp-CCAP) was identified in the commercially important mud crab Scylla paramamosain, which could be processed into four CCAP associated peptides and one mature peptide (PFCNAFTGC-NH2). Bioinformatics analysis indicated that Sp-CCAP was highly conserved in crustaceans. RT-PCR results revealed that Sp-CCAP was expressed in nerve tissues and gonads, while Sp-CCAP receptor gene (Sp-CCAPR) was expressed in 12 tissues of S. paramamosain, including hepatopancreas. In situ hybridization further showed that Sp-CCAPR positive signal mainly localized in F-cells of hepatopancreas. Moreover, the mRNA expression level of Sp-CCAPR in the hepatopancreas was significantly up-regulated after lipopolysaccharide (LPS) or polyriboinosinic polyribocytidylic acid (Poly (I:C)) challenge. Meanwhile, the mRNA expression level of Sp-CCAPR, nuclear transcription factor NF-κB homologues (Sp-Dorsal and Sp-Relish), member of MAPK signaling pathway (Sp-P38), pro-inflammatory cytokines factor (Sp-TNFSF, Sp-IL16) and antimicrobial peptide (Sp-Lysozyme, Sp-ALF, Sp-ALF4 and Sp-ALF5) in the hepatopancreas were all up-regulated after the administration of synthetic Sp-CCAP mature peptide both in vivo and in vitro. The addition of synthetic Sp-CCAP mature peptide in vitro also led to the increase of the nitric oxide (NO) concentration, and improved bacterial clearance ability in the hepatopancreas culture medium. The present study suggested that Sp-CCAP might be involved in the hepatopancreas immune responses of S. paramamosain by activating immune molecules through receptor-mediated signaling pathways. Collectively, our findings shed new light on neuroendocrine-immune regulatory system in arthropods, and could potentially provide a new strategy for disease prevention and control for mud crab aquaculture.